Eletrodeposição de ligas bioabsorvíveis do sistema Fe-Mn - Figueira, Gustavo (2019)
Stents are medical devices which promote the opening and mechanical support of clogged blood vessels and, once applied, cannot be removed. The manufacture of bioabsorbable stents is desirable to avoid several subsequent clinical complications, such as restenosis. Bioabsorbable metallic stents manufactured with iron-based alloys deserve prominence due to the very low toxicity and good compromise between mechanical strength and ductility. However, the corrosion resistance of these alloys is still very high compared to the lifetime of the stent. Such properties, coupled with the modification of the Fe corrosion rate by the addition of alloying elements, shows the potential of this system in the manufacture of stents. In this context, the objective of this project is to evaluate the manufacture of Fe-Mn-based alloys by means of electrodeposition, especially the process parameters and their influence on the surface morphology and microstructure. The samples were obtained by electrodeposition from a base electrolyte of 0.4 M FeCl2 + 0.4 M MnCl2, with the addition of additives such as ammonium chloride, sodium saccharin and sodium dodecyl sulfate. The deposits with the best surface quality were analyzed by Scanning Electron Microscopy, Energy Dispersive X-Ray Spectroscopy and X-Ray Diffraction. The results indicated that the simultaneous deposition of Fe-Mn in potentials beyond -1.7 V vs. Ag/AgCl results in the formation of a dendritic microstructure, also leading to the presence of defects such as porosity and cracks. On the other hand, the addition of ammonium chloride allows the incorporation of higher Mn content with lower values of potential, maintaining the formation of a homogeneous microstructure and with lower level of defects. Sodium saccharin and sodium dodecyl sulfate were also effective in improving the surface quality of the deposit, indicating that the use of additives is indispensable in obtaining Fe-Mn alloys obtained by electrodeposition.